Práctica del sexting en la relación de pareja de adultos jóvenes - Moncayo Romero, Marjuri Adelaida (2024)
Nowadays the practice of sexting has revolutionized in recent years, especially among young adults who have access to digital devices; this practice of sexting can be consensual, increasing affective and sexual satisfaction in couple relationships, but it can also lead to problems if the images or messages fall into the wrong hands, resulting in extortion, the present study used a quantitative approach with a non-experimental crosssectional design had a documented collection development about the practice of sexting in couple relationships in young adults; at the beginning of the research, we found 429 scientific articles developed between 2013 and 2023, to determine the sample, we followed a non-probabilistic sampling; the selection depended on exclusion and inclusion criteria, through which we selected 14 documents related to the topic under investigation, we used the prism instrument to examine various sources of information, including scientific articles, meta-analyses, cohort studies, and descriptive and analytical studies with quartiles from 1 to 4 according to the Scimago Journal Rank; based on the general objective to describe the scientific evidence on how the practice of sexting presents in the relationship of young adult couples, we concluded that more than half of the population have practiced sexting, with a higher frequency of intimate photographs, text with sexual content and videos with erotic/sexual content, with the highest prevalence in Spain, Mexico, Nicaragua, Peru and Rome, as for the consequences, extortion and affective and sexual satisfaction were the most prevalent in all the studies, we designed an informative guide that aims to understand the advantages and risks of sexting, to make informed and responsible decisions, and to present intervention strategies at a preventive level